Ultrasound‐Activated Sensitizers and Applications - Lin, Xiahui; Song, Jibin; Chen, Xiaoyuan; Yang, Huanghao (Angewandte Chemie International Edition, 2020)
Modalities for photo‐triggered anticancer therapy are usually limited by their low penetrative depth. Sonotheranostics especially sonodynamic therapy (SDT), which is different from photodynamic therapy (PDT) by the use of highly penetrating acoustic waves to activate a class of sound‐responsive materials called sonosensitizers, has gained significant interest in recent years. The effect of SDT is closely related to the structural and physicochemical properties of the sonosensitizers, which has led to the development of new sound‐activated materials as sonosensitizers for various biomedical applications. This Review provides a summary and discussion of the types of novel sonosensitizers developed in the last few years and outlines their specific designs and the potential challenges. The applications of sonosensitizers with various functions such as for imaging and drug delivery as well as in combination with other treatment modalities would provide new strategies for disease therapy. A sound approach: Photo‐triggered anticancer therapeutic modalities are usually limited by their low penetrative depth. An alternative approach is sonodynamic therapy (SDT), which uses high‐penetrating acoustic waves to activate sound‐responsive materials. This Review gives a summary and discussion of such sonosensitizers.